Automated Maintenance System For Freshwater Aquascape Based On The Internet Of Things (Iot) - El Hakim, Elang Bayu; Aryanto, Joko (Universitas PGRI Semarang, 2024)
Aquascaping is a hobby that has gained considerable popularity across different age groups, from young to old. Aquascaping itself is the art of arranging plants, water, rocks, coral, wood and other natural elements in glass or acrylic containers. One of the main obstacles in the world of aquascaping is consistency, which is often difficult to achieve when the owner has a busy schedule or limited time. Without the implementation of Internet of Things (IoT) technology and microcontrollers connected to mobile applications, this drawback is even more pronounced. The inability to maintain consistency in maintenance can lead to a decline in aquascape quality, both in terms of aesthetics and ecosystem health. Therefore, an innovative system using IoT is expected to provide a smart solution to overcome the major shortcomings of aquascape maintenance and enhance the experience of this hobby for its enthusiasts..